2013
DOI: 10.1039/c3cp52484a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability studies of mixed monolayers of saturated and unsaturated phospholipids under low-level ozone

Abstract: In the present study, stability and structure of single and binary mixed monolayers of an unsaturated phospholipid, DOPC, and a saturated phospholipid, DPPC-d75, on the water surface, were explored using the π-A isotherm, atomic force microscopy (AFM) and sum frequency generation (SFG) vibrational spectroscopy in various environments. Our results demonstrated that DOPC in the monolayers becomes unstable after the exposure to a low concentration of ozone (20 ± 10 ppb) or even to ambient laboratory air, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 44 publications
11
57
0
Order By: Relevance
“…Several studies by Finlayson-Pitts and co-workers have shown that unsaturated phospholipids are readily oxidized by O 3 from the “top down” to generate secondary ozonides and a number of products. 122124 The group of Ye 125,126 probed the structure and stability of phospholipids in low ozone concentration by a combination of π–A isotherms, vibrational spectroscopy, and force microscopy. Their results demonstrate that the CC moieties in the unsaturated lipids are selectively oxidized by a trace amount of ozone in the ambient environment.…”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%
“…Several studies by Finlayson-Pitts and co-workers have shown that unsaturated phospholipids are readily oxidized by O 3 from the “top down” to generate secondary ozonides and a number of products. 122124 The group of Ye 125,126 probed the structure and stability of phospholipids in low ozone concentration by a combination of π–A isotherms, vibrational spectroscopy, and force microscopy. Their results demonstrate that the CC moieties in the unsaturated lipids are selectively oxidized by a trace amount of ozone in the ambient environment.…”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%
“…The present results suggest that the unsaturated phospholipids can be selectively oxidized by a trace amount of ozone in the ambient environment, while the oxidation of DOPC is partially inhibited by the presence of DPPC in the mixed monolayers . We are continuing to study the structure and stability of different unsaturated lipid molecules in a variety of environments.…”
Section: Probing Structural Changes At Biointerfacesmentioning
confidence: 64%
“…Figure shows SFG spectra of a DOPC monolayer prepared in (a) nitrogen and (b) low‐level ozone environments (black squares) . The SFG spectrum after exposure to ozone is significantly different from that in nitrogen.…”
Section: Probing Structural Changes At Biointerfacesmentioning
confidence: 99%
See 2 more Smart Citations